Congenital Malformation Among Newborns at Dr. Pirngadi Hospital Medan During 1981 1984 - Bidasari Lubis; Guslihan Dasa Tjipta; Arman J. O. Panjaitan; Noersida Raid; Helena Siregar (Indonesian Pediatric Society, 1989)
A study of the incidence of congenital malformation had been assessed among 15185 newborns delivered in the Neonatal Unit Dr. Pirngadi Hospital Medan during 1981-1984. Still-births were not included in this study.Out of these 15185 newborns there were 77 cases (0.51%) of congenital malformation. The four leading malformations were: pes-equinovarus 7 cases (9. 1 %), labiognathopalatoschizis, hidrocephalus and anencephalus 6 cases each (7.7%).The number of congenital malformation was higher in the age group of mothers older than 35 years (0. 78%) and in the group of babies born in the birth order as third and further (53.85%) and as first born babies (33.33%).From 77 cases with congenital malformation only 2 (2.56%) were operated soon after birth, while 49 cases (64.1%) went home without surgical intervention, and 28 cases (15.9%) died during hospitalization.